Ultra-high doses tests on 28nm CMOS technology for high energy physics application - Ciachera, Geoffrey (2024)
This work is about the qualification of next generation of electronics detectors for high energy physics application. A new upgrade of the Large Hadron Collider, designated as High Luminosity Large Hadron Collider, is scheduled for completion around 2030 and applications specific integrated circuits will be exposed to new ultra-high radiation radiations levels. In comparison to the Large Hadron Collider, where the maximum expected total ionizing dose is limited to a few tens of Mrad after 10 years of experiment, while the high luminosity maximum radiation dose is predicted to be significantly higher for certain chips, reaching above 2.5 Grad. This total ionizing dose is approximately a hundred times greater and reaches new horizons in radiation electronics engineering. In this study, the 28nm complementary metal-oxide semiconductor has been subjected to testing thanks to specific chip that allow to irradiated single diode or transistors. In Chapter 3, three tests were conducted on diode inside field oxides field effect transistor structure. The first test reaches a 1Grad total ionizing dose while the other two only 100Mrad. The second and third test were made at different biases and temperatures respectively. Results of these tests indicate that the damage to the diode is greater when the applied voltages and temperature conditions are higher. The second test was conducted on transistors, and different transistors sizes i.e. W/L = 100/30 𝑛𝑚 and W/L = 3/0.03 𝜇𝑚 and W/L = 0.1/1 𝜇𝑚 where W and L stand for the width (W) and the length (L) of the transistors respectively. These transistors were subjected to irradiation at a total ionizing dose of 5 Grad with the objective of evaluating their survivability. As a result, all n-doped and p-doped metal oxide semi-conductor transistors survived i.e. a significant current from drain to source is flowing, except the long and narrow p-doped devices which reached a degradation of 99%. Finally, n-doped device got a strong increase in the leakage current between 10 thousand to 1 million more than the pre-irradiation one. Overall, the 28 nm complementary metal oxide semi-conductor is a promising technology to make application specific integrated circuits for new detectors generation for high energy physics applications. However, this report is not exhaustive and a lot of more tests are needed.